Influences of pH Values on Magnetic CoNiP Nanowires Fabrication - Thiem, Luu Van; Tu, Le Tuan; Thang, Pham Duc (VNU Journal of Science: Mathematics - Physics; Vol 30 No 2, 2014)
Abstract: CoNiP nanowire arrays were fabricated by electrodeposition method into polycarbonate (PC) templates at different pH values. It is obvious that the crystal structure of the CoNiP nanowires depends on the pH values of electrolyte. The XRD results show that crystal structure of the CoNiP nanowires is hcp structure and the intensity of the hcp (002) increased enhances as solution pH=3.5. Magnetic measurements indicate that CoNiP nanowires show a transition from soft to hard magnetic properties with pH values from 2.0 to 3.5 and the maximum coercivity is 1630 Oe. Keywords: PC template, CoNiP nanowires, magnetic properties and electrodeposition.